Persistent fifth aortic arch: a comprehensive literature review - Shan, Haiyan; Du, Xiaolan; Zheng, Guangrong; Ke, Tengfei; Liao, Chengde; Yang, Haiyan (Frontiers in Pediatrics, 2023)
Persistent fifth aortic arch (PFAA) is an exceedingly rare congenital cardiovascular anomaly that occurs when the fifth aortic arch not degenerating during the embryonic, which is also associated with various cardiovascular anomalies. There are continuously individual case reports were reported after it was first reported in 1969 by Van Praagh. To our best knowledge, PFAA is usually with a high rate of misdiagnosis and missed diagnosis in clinical because of its rarity and incomprehensive understanding. The purpose of this review is to summarize the embryonic development, pathological classification, imaging diagnosis and clinical treatment of PFAA to improve its comprehensive understanding and allow for diagnostic accuracy and treatment.